Photo‐Induced Discoloration and the Corresponding Mechanism of Benzotrifuroxan under UV Irradiation. Issue 4 (27th January 2022) - Fu, Xiaolin; Chen, Jian‐Bo; Zhuang, Siqi; Huang, Bing; Liu, Yu; Wang, Junxia; Yang, Shiyuan
Abstract: Benzotrifuroxan (BTF) as a powerful and hydrogen‐free explosive discolors under UV irradiation, but the process remains unclear. Herein, we comprehensively investigated the photochemical process and mechanism of BTF under UV irradiation. A pink color is observed in BTF after irradiation with 365‐nm light, while BTF becomes brown by 254‐nm light. Besides BTF, compound 1 is detected by ultrahigh‐performance liquid chromatography after UV irradiation. Compound 1 is prone to be yielded under 254‐nm irradiation compared to 365‐nm irradiation. Meanwhile, it is easier for the formation of compound 1 in BTF solution rather than solid BTF. Additionally, a small amount of compound 2 is found in BTF solution after 254‐nm irradiation over 120 min. A new photodegradation pathway of BTF is proposed through high‐resolution mass spectrometry. Compound 1 is produced as the main product through the isomerization of the N ‐oxide of BTF, and BTF also loses NO to yield compound 2. Through the analysis of scanning electron microscopy, BTF exhibits different crystal structures between 365‐nm irradiation and 254‐nm irradiation. Nano holes are widely observed in solid BTF after 365‐nm irradiation, but these holes disappear under 254‐nm irradiation. Thus, the differences originating from the content of compound 1 and the crystal structure of BTF may lead to the discoloration of BTF under UV irradiation. Abstract :